ASPECTS OF PUBLIC UTILITY INCOME AND EXPENSE. - Taylor, P. C. (The Accounting Review, 1927)
Abstract Public utilities have given rise to many knotty problems, and much comment has been heard, pro and con, as to the reasonableness of their income and expenses. A public utility is commonly thought of as a natural monopoly, but a regulated one, which does not settle its own rates. It is under the jurisdiction of the various regulatory commissions which are found in all states with the exception of Delaware and Kentucky. These commissions are supposed to set the utility rates at that point which will yield a reasonable rate of return on "fair value," plus enough to cover operating expense., but the more or less familiar discussions and decisions as to what "fair value" and a reasonable rate of return are, and the methods of determining them, will be passed by here. Instead, it is proposed that the gross, net operating, and net income of the utilities be examined in their relation to some of the other values and costs, and that some of the major operating expenses be subjected to a survey as to what they include, their reasonableness, and their relation to total operating expenses.